2012
DOI: 10.1590/s0074-02762012000500016
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus quantification in serum and saliva of HCV-infected patients

Abstract: The hepatitis C virus (HCV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Other studies found that living with a family member infected with HCV [34,35] or suffering from liver disease [33,36,37] was an associated risk factor. Although it is known that multiple factors contribute to HCV transmissibility for saliva [5,38] and viral loads are very low in this [39]. The presence of HCV in saliva is to draw attention mainly in patients with active infection and high viral loads, patients who require guidance on their oral health by dentist.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that living with a family member infected with HCV [34,35] or suffering from liver disease [33,36,37] was an associated risk factor. Although it is known that multiple factors contribute to HCV transmissibility for saliva [5,38] and viral loads are very low in this [39]. The presence of HCV in saliva is to draw attention mainly in patients with active infection and high viral loads, patients who require guidance on their oral health by dentist.…”
Section: Discussionmentioning
confidence: 99%
“…The literature (2)(3)(4)(5) refers to the presence of RNA-HCV in body fluids such as saliva, peripheral lymph nodes and semen. It is worth noting that although the virus is found in low titrations, this form of transmission must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…There are innumerable studies on the presence of RNA-HCV in the saliva (2)(3)(4)(5) but their results vary, reflecting the heterogeneity of the populations studied, and the variety of detection techniques used. Nevertheless, epidemiological studies suggest that the infectious capacity of viral particles of HCV in the saliva is low.…”
mentioning
confidence: 99%
“…Some authors have the HCV as a virus with a triple tropism (Hepatotropism, lymphotropism, and sialotropism), which could explain the xerostomia in these patients [14]. In addition, the reduced salivary flow rate (hyposalivation) in Hepatitis C patients could be due to infiltration of the salivary gland by the virus [12] or to a possible virus induced immune mechanism [22,23]. However, in only 3 cases (12.5%) xerostomia and hyposalivation were observed, simultaneosly.…”
Section: Discussionmentioning
confidence: 99%